Detective Genre in the West and in Russia - Osmukhina, Olga; Gudkova, Svetlana (Journal of History Culture and Art Research, 2020)
The article is devoted to the study of the history of the detective genre in literature formation. The term "detective" is still controversial in literature studies. Academicians distinguish different subgenres of detective works, in this case taking into account synthesis of storyline model of psychological, adventurous, and spying novels. An important feature of the detective genre is the completeness of the facts: the solution of the mystery cannot be based on the information that was not provided to a reader during the investigator’s description. Hence, readers should have enough information to find a solution on their own. Studies on detective genre have appeared in the West first. Its arrival to Russia occurred in the 1990s. The authors analyze the theoretical works devoted to the detective genre, identify the most important features of the classic and postmodern detective genre, as well as identify the key steps in the formation of literature on detective genre. The article states that the founder of the detective genre was E. A. Poe. Then this genre has developed in England (A. Conan Doyle, A. Christie), in France (S. Japrisot, Georges Simenon), the U.S. (Hammett, Chase), and Russia (R. Ovals, R., Kim, Y. Semenov, br. Weiners, D. Koretsky, N. Leonov, B. Akunin, etc.). Herewith, during the transition to the 21st century, this genre has experienced significant changes regarding the leading character: a hero is not a police officer but an amateur investigator with a strong personality, analytical mind and outstanding abilities.